A multidisciplinary approach to the clinical management of Prader–Willi syndrome. Issue 3 (29th January 2019) - Duis, Jessica; van Wattum, Pieter J.; Scheimann, Ann; Salehi, Parisa; Brokamp, Elly; Fairbrother, Laura; Childers, Anna; Shelton, Althea Robinson; Bingham, Nathan C.; Shoemaker, Ashley H.; Miller, Jennifer L.
Abstract: Background: Prader–Willi syndrome (PWS) is a complex neuroendocrine disorder affecting approximately 1/15, 000–1/30, 000 people. Unmet medical needs of individuals with PWS make it a rare disease that models the importance of multidisciplinary approaches to care with collaboration between academic centers, medical homes, industry, and parent organizations. Multidisciplinary clinics support comprehensive, patient‐centered care for individuals with complex genetic disorders and their families. Value comes from improved communication and focuses on quality family‐centered care. Methods: Interviews with medical professionals, scientists, managed care experts, parents, and individuals with PWS were conducted from July 1 to December 1, 2016. Review of the literature was used to provide support. Results: Data are presented based on consensus from these interviews by specialty focusing on unique aspects of care, research, and management. We have also defined the Center of Excellence beyond the multidisciplinary clinic. Conclusion: Establishment of clinics motivates collaboration to provide evidence‐based new standards of care, increases the knowledge base including through randomized controlled trials, and offers an additional resource for the community. They have a role in global telemedicine, including to rural areas with few resources, and create opportunities for clinical work to inform basic and translational research. As a care team, we are currently charged with understanding the molecular basis of PWS beyond the known genetic cause; developing appropriate clinical outcome measures and biomarkers; bringing new therapies to change the natural history of disease; improving daily patient struggles, access to care, and caregiver burden; and decreasing healthcare load. Based on experience to date with a PWS multidisciplinary clinic, we propose a design for this approach and emphasize the development of "Centers of Excellence." We highlight the dearth of evidence for management approaches creating huge gaps in care practices as a means to illustrate the importance of the collaborative environment and translational approaches. Abstract : Unmet medical needs of individuals with Prader–Willi syndrome make it a rare disease that models the importance of multidisciplinary approaches to care with collaboration between academic centers, medical homes, industry, and parent organizations. Establishment of centers motivates collaboration of experts to provide evidence‐based new standards of care, increases the knowledge base regarding success of treatments through randomized controlled trials, and offers an additional resource for patient and family concerns.